Deformation and failure characteristics of soft rock tunnel surrounding rock under mining and water immersion conditions - XIE Panshi; FANG Jiarui; HU Bosheng; ZHANG Bo; ZHANG Xi; DUAN Siyu (Gong-kuang zidonghua)
The deformation and failure of surrounding rock in soft rock tunnels are significantly exacerbated by the combined effects of mining activities and water immersion erosion. Water immersion leads to the failure of anchoring agents, which reduces the anchorage strength of bolts and cables, thereby diminishing their load-bearing capacity and severely compromising the safety of the tunnel face. To address this issue, a research methodology integrating physical similarity simulation experiments, numerical simulations, and field measurements was employed. The study investigated the failure characteristics of water-immersed soft rock tunnel surrounding rock under mining influence and varying support parameters. The deformation and failure characteristics of surrounding rock under mining and water immersion were identified, and optimal support parameters were proposed. Experimental results indicated that, under mining influence, the deformation and failure of surrounding rock in soft rock tunnels exhibited asymmetry, and under water immersion, the failure range of the surrounding rock expanded further. Increasing the length of the anchor cable from 9 m to 10 m resulted in a 4.3% reduction in the failure range of surrounding rock. When a 12.2 m anchor cable was used to support roof, the failure range on both sides was larger than when using the 9 m or 10 m cables. This was mainly because the 12.2 m cable reached the water-bearing layer in the roof, leading to increased water seepage and further softening of the surrounding rock. The use of a combined support system, consisting of a 9.2 m anchor cable and a 4.2 m short anchor cable, led to a reduction in the surrounding rock's failure range and a significant improvement in water seepage conditions compared to the previous support schemes. Field application results demonstrated that the combined support system, comprising a 9.2 m anchor cable and a 4.2 m short anchor cable, reduced roof subsidence, sidewall deformation, and floor uplift by 77.5%, 65%, and 76.5%, respectively, compared to the original support parameters. This effectively enhanced the surrounding rock's resistance to deformation and failure.